Reduction of Blood Pressure Throught Exercises Among Elderly with Hipertension - Solihin Solihin; Neny Setia Ningsih; Stevany Sholikhah; Tri Aulianta Mangunsong; Emanuel Emartinus Giawa; Kristina L Silalahi (LPPM STIKES KENDAL, 2020)
Hypertension causes morbidities for everyone especially in elderly. In the management of hypertension in cardiovascular disease, one of the non-pharmacological aspects is physical activity, one of which is elderly exercise, which can reduce the risk of lipid buildup in the walls of blood vessels and maintained elasticity thereby increasing cardiac physiology and lowering blood pressure. The purpose of this study was to identify the effect of elderly exercise on reducing blood pressure in hypertensive patients. Quantitative study with One Group Pre-Posttest Design. The sample consisted of 45 elderly with hypertension. The study was conducted on May 12-16, 2020. The intervention carried out was elderly exercise for 3 times, the value of blood pressure measurement was recorded on the observation sheet. Data analyzed used paired t-test. The results obtained p = 0,000 (P <0.05) that there are differences in systole and diastole blood pressure before and after elderly gymnastics. The importance of the elderly to do regular exercise to reduce and reduce the presence of hypertension complaints.